Viscous dissipation effect for Al2O3-Ag/water hybrid nanofluid in mixed convection: A numerical analysis - Elfiano, Eddy; Hastuti, Kurnia; Rahman, Jhonni; Prasetyo, Ari; Nik Mohd Izual, Nik Ibrahim; Mohamed, Muhammad Khairul Anuar (IOP Publishing, 2025)
The mathematical model of the viscous dissipation effect on the mixed convection boundary layer flow in a horizontal circular cylinder in a hybrid nanofluid composed of alumina Al2O3 and nanofluid Ag/water was investigated in this study. The transformed partial differential equations are numerically solved using the Keller-box method, an implicit finite-difference approach. Numerical approaches facilitate the calculation of the reduced Nusselt number, local skin friction coefficient, velocity, and temperature profiles. The current study evaluates flow properties under a variety of Eckert number and mixed convection parameters. The Eckert number values reflect viscous dissipation. this process converts kinetic energy into internal energy, which causes the fluid to heat up. It is found that the greater the Eckert number, the more likely heat transfer will occur at a faster rate. Meanwhile The high kinetic energy velocity of the hybrid nanofluid creates significant surface friction, raising the temperature. The findings of this publication are both insightful and significant, offering valuable contributions to researchers investigating boundary layer motion